Sistemática e história evolutiva de Ergasilidae (Crustacea: Copepoda; Cyclopoida). [Systematics and evolutionary history of Ergasilidae (Crustacea: Copepoda; Cyclopoida).] - Marques Orsi, T.M. (203 pp. [In Portuguese and English], 2018)
Ergasilidae is one of the largest families among Copepoda parasites, being considered one of the most common parasitizing marine fishes but is quite common in continental environments as well. However, as for most animals, it is believed that the ergasilide fauna is still very little known. The family presents a great diversity of species, a total of 261 species and 29 valid genera. Among them is Ergasilus being this the most representative genus of the family. Previous studies have shown that Ergasilidae is present in all continents except Antarctica, and in several salinity regimes. They mostly use fish as hosts, but they are also present in mollusks. They have been reported in 25 different orders of fish, both marine and continental. The present study was divided into three chapters. The first chapter aimed to propose a phylogenetic hypothesis using a combination of morphological data, 18S rDNA and 28S rDNA, to review the diagnoses and composition of genera considered valid in Ergasilidae, and to present a dichotomous key for the genera of the family. In addition, a dichotomous key of the Neotropical species of Ergasilidae is presented. In this chapter two ribosomal molecular markers were used to propose a phylogenetic hypothesis for the family, for which 24 representatives of 8 genera of Ergasilidae were identified and sequenced, being a new genus. The second chapter aims to test whether the exchange of hosts by Ecological fitting is a driver of diversity in the family. For this, the historical patterns of host-parasite relationship and their geographical distribution were reconstructed using the hypothesis derived from the Bayesian analysis of 54 species of Ergasilidae presented in chapter 1; and the host families and geographic distribution of the species included were mapped in the Ergasilidae phylogeny using the Liebermann algorithm. It was observed that expansion and isolation events were most often associated with incorporation (expansion) or immediate exchange of hosts (isolation). Finally, the third chapter aimed to describe, illustrate and propose new taxa that were found during the development of the work as a whole. Despite the possible limitations associated with sample density in this study, it is clear that the pattern of Ergasilidae diversification is more dynamic than that which would be putatively proposed by the school of maximum co-speciation. The diversification of the Ergasilidae seems to have proceeded by taking advantage of the opportunities of colonization and dispersion conferred by their hosts than by a passive process of diversification. Key-words: Ergasilidae, taxonomy, phylogeny